2020
DOI: 10.1108/jmtm-11-2019-0417
|View full text |Cite
|
Sign up to set email alerts
|

Linking industrial agglomeration and manufacturers inventory performance: the moderating role of firm size and enterprise status in the supply chain

Abstract: PurposeFrom the intra- and inter-regional dimensions, this paper investigates the linkage between industrial agglomeration and inventory performance, and further demonstrates the moderating role of firm size and enterprise status in the supply chain on this linkage.Design/methodology/approachUsing a large panel dataset of Chinese manufacturers in the Yangtze River Delta for the period from 2008 to 2013, this study employs the method of spatial econometric analysis via a spatial Durbin model (SDM) to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 83 publications
(260 reference statements)
0
8
0
Order By: Relevance
“…In a more detailed view, previous studies demonstrated that large firms have more innovative capabilities because they have more resources and know-how (Sánchez-Torné et al , 2020; Wang et al , 2020). Also, they have a better structure to support any failure when implementing innovation.…”
Section: The Moderating Role Of Companies Sizementioning
confidence: 99%
“…In a more detailed view, previous studies demonstrated that large firms have more innovative capabilities because they have more resources and know-how (Sánchez-Torné et al , 2020; Wang et al , 2020). Also, they have a better structure to support any failure when implementing innovation.…”
Section: The Moderating Role Of Companies Sizementioning
confidence: 99%
“…Will the size of a company unobtrusively affect the interaction of corporate resources? Firm size can be proxied by the total assets of a firm (Wang et al , 2020). Differently sized firms may have distinct board independence levels and generate different preferences for IC, thereby leading to varying firm performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Several researchers have emphasized the controlling effect of firm size on manufacturing performance (e.g. da Silveira and Sousa, 2010; Wang et al. , 2020).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Studies show that small businesses could not be considered the scaled-down counterparts of the larger ones (e.g. Wang et al. , 2020).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation